Salary disparity and gender in the central zone of Peru - Arroyo Yupanqui, Marco Antonio (2022)
Wage disparities between men and women in both the formal and informal sectors in the central macro-region of Peru is a latent reality despite the constant concern of the government and social organizations in the country to reduce these wage gaps; Therefore, it is the subject of study and analysis in this research. In this sense, the established objective was to analyze the salary differences between men and women who work in the formal and informal sectors in the central macro region of Peru, for which ENAHO data and a methodology established by Mincer, Oaxaca-Blinder were used. and the Probit model that has allowed reaching the results that confirm the existence of a disproportionate salary disparity in the formal sector. This is because both men and women in the formal sector are better paid, but men are paid relatively more than women. The salary gap in the informal sector is small since the informal salary of men and the informal salary of women is almost homogeneous.